2015
DOI: 10.1016/j.conb.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The thalamocortical network as a single slow wave-generating unit

Abstract: During non-REM sleep the EEG is dominated by slow waves which result from synchronized UP and DOWN states in the component neurons of the thalamocortical network. This review focuses on four areas of recent progress in our understanding of these events. Thus, it has now been conclusively demonstrated that the full expression of slow waves, both of natural sleep and anesthesia, requires an essential contribution by the thalamus. Furthermore, the modulatory role of brainstem transmitters, the function of cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
144
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(152 citation statements)
references
References 66 publications
(67 reference statements)
5
144
1
Order By: Relevance
“…Low-frequency activity is a key contributor to integrate longrange interactions within thalamocortical-thalamic networks (21,(51)(52)(53). A recent study investigated the relationship between single neuron spiking activity and brain-wide cortical calcium dynamics (54).…”
Section: Discussionmentioning
confidence: 99%
“…Low-frequency activity is a key contributor to integrate longrange interactions within thalamocortical-thalamic networks (21,(51)(52)(53). A recent study investigated the relationship between single neuron spiking activity and brain-wide cortical calcium dynamics (54).…”
Section: Discussionmentioning
confidence: 99%
“…However, empirical data and analyses to evaluate this hypothesis have been lacking. The role of the thalamus in generating slow and δ oscillations observed during nonrapid eye movement sleep and some states of anesthesiainduced altered consciousness has been a topic of much debate (21). Recordings in deafferented cortex show that slow oscillations can occur in the absence of thalamic connections (22).…”
Section: Layers Of Prefrontal Cortex Are Differentially Affected By Pmentioning
confidence: 99%
“…Electroencephalogram (EEG) recordings in humans during gradual induction of unconsciousness with propofol show the appearance of frontal β oscillations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) at the onset of sedation, followed by the appearance of coherent frontal α (8-12 Hz) oscillations (7)(8)(9)(10) and widespread slow (0.1-1 Hz) and δ (1-4 Hz) oscillations (7,11,12) when subjects no longer respond to sensory stimuli. Biophysical models of neuronal dynamics have shown that whereas α and β oscillations can be generated by propofol's actions in cortex alone (13), coherent α oscillations require the participation of both thalamus and cortex (14).…”
mentioning
confidence: 99%
“…Thalamocortical unit activity underlies the generation of slow oscillation, one of the most important brain processes participating in generation of sleep (Crunelli et al, 2015). Slow wave activity in humans showed alternating neuronal excitation and inhibition patterns identified previously in animal models as upstates and downstates Csercsa et al, 2010;Nobili et al, 2012;Peyrache et al, 2012;Staba, C. L. Wilson, Bragin, Fried and Engel, 2002a).…”
Section: Testing Normal Functions In Epileptic Patientsmentioning
confidence: 75%